Intersubjectivity: Conceptual Considerations in Meaning-Making With a Clinical Illustration - Harrison, Alexandra; Tronick, Ed (Frontiers in Psychology, 2022)
This paper explores intersubjectivity through a discussion of humans as meaning makers. In psychotherapy and in other more commonplace human interactions, humans are constantly making meaning. They make meaning of their experience with the inanimate world, with other living creatures, and with themselves. We propose an open dynamic systems model of development through meaning-making. We will elaborate the view of intersubjectivity as central to human development with a presentation of the scientific paradigm of the Face-to-Face Still-Face, in which we can observe the intersubjective process between infant and parent. We will also illustrate our points with excerpts from the analytic treatments of a young child on the autistic spectrum. In the case of ASD children, the challenges in establishing an intersubjective state highlight critical features of the concept of intersubjectivity.